Selfhood and Individuality in Dōgen’s Thought - Rein Raud (Religions)
The article addresses one of the central issues of Buddhist thought, the status of selfhood and individuality, as they are discussed in the work of the Japanese Zen thinker Dōgen (1200–1253). It discusses critically and rejects the widespread assumption that Dōgen postulates two levels of selfhood, that of the deluded individual and a transcendent True Self to the attainment of which one should aspire. On the basis of rigorous methodological principles, formulated at the outset, the article analyzes in detail the terminology Dōgen uses for selfhood and individuality and provides a comprehensive, coherent interpretational framework for the reading of a number of key passages that have usually been presented in support of the True Self theory.